Interaction between Economic Education and Strategic Planning in the New Complexity of the Social Life - Gheorghe H. Popescu; Elvira Nica (Theoretical and Applied Economics, 2006)

(untitled)
The economic education, together with the other forms of the integral education, serves to an uninterrupted struggle of the man with the nature and with the society from inside him, within the micro-cosmos where he lives near by other living being, searching the ascension by means of permanent and active adaptation to the external world requirements, as a products of the social communion feeling. In the field of the economic education also, there is a problem to put in concordance the education system with the amount of knowledge in an almost explosive expansion. Such a problem could become really dramatic one if the today didactic technology had not developed a process of simplification by means of an essence transmitting and appropriating the knowledge.